Presidential form of government of the Republic of Kazakhstan: theoretical and legal aspects (Journal of actual problems of jurisprudence, 2018)
The authors of this article examines the presidential form, the Management Board of the Republic of Kazakhstan: the theoretical and legal aspects. An important feature of the formation of presidential power in Kazakhstan is a constant process of development and modernization, along with other state institutions.Key words: Power, President, government, law, state.